2017
DOI: 10.1080/17439760.2017.1402076
|View full text |Cite
|
Sign up to set email alerts
|

Happy-productive groups: How positive affect links to performance through social resources

Abstract: The current study extends the Broaden & Build Theory to the collective (i.e., groups) level of analysis, focusing on the mediating role of group social resources (i.e., cohesion, coordination, teamwork, supportive team climate) between group positive affect (i.e., enthusiasm, optimism, satisfaction, comfort) and group performance (i.e., inand extra-role performance, creative performance). To test our hypotheses, we conducted two studies using independent samples. Study 1 is a laboratory study with 449 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 79 publications
7
57
0
4
Order By: Relevance
“…On the other hand, unlike the aforementioned authors, it has been considered that the relationship is not direct, but rather mediated by the effect of the variables. Based on Broaden and Build Theory [ 91 , 92 ], team resilience [ 15 ] and group social resources [ 13 ] were considered as an underlying mechanism connecting group positive affect to team performance. Thus, groups that experience positive affect grow with adversity and reinforce their social bonds which allows them to complete both the required tasks and those that are not required formally by the job.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, unlike the aforementioned authors, it has been considered that the relationship is not direct, but rather mediated by the effect of the variables. Based on Broaden and Build Theory [ 91 , 92 ], team resilience [ 15 ] and group social resources [ 13 ] were considered as an underlying mechanism connecting group positive affect to team performance. Thus, groups that experience positive affect grow with adversity and reinforce their social bonds which allows them to complete both the required tasks and those that are not required formally by the job.…”
Section: Resultsmentioning
confidence: 99%
“…As far as we know, this relationship has commonly been called the happy-productive worker [ 97 ], and it has been analyzed from multiple perspectives and areas [ 98 , 99 ]. Based on happy-productive worker research and group theories, some authors have started a new research about happy-productive group [ 13 , 22 ] with promising results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Kim & Shin [80] found that cooperative group norms and group positive affect were significant predictors of team creativity, and that this relationship was fully mediated by collective efficacy (i.e., a sense of collective competence shared among team members with respect to responding to specific situational demands and allocating, coordinating, and integrating their resources). Peñalver et al [81] found full-mediation effect of group social resources (i.e., teamwork, coordination, supportive team climate) between group positive affect and in-and extra-role performance.…”
Section: Operationalization Of Collective Satisfactionmentioning
confidence: 99%
“…Additionally, group emotion influences team processes and outcomes [8]. For example, an increase in positive mood will lead to greater cooperativeness and less group conflict [9]. On the other hand, from the perspective of computer vision, consider the mood of a family posing for a group photograph at a wedding party, it is expected that there is an automated system recognizing the mood of the family.…”
Section: Introductionmentioning
confidence: 99%